The family business and its importance in Ecuador - Gonçalves do Espirito Santo, Joaquím (2024)
The family business is a central institution in the Ecuadorian economy. In Ecuador, as in the rest of the world, family businesses are generators of wealth, employment, and innovation. Family businesses worldwide are the main driving force of the economy, created with the purpose of generating new jobs and wealth. However, they need to strengthen and establish strategies to survive and endure. The purpose of this paper is to demonstrate the importance and benefits that the family business generates as a driving force for the national economy and the need for the State to promote its continuity and permanence over time.